2015
DOI: 10.3390/f6114001
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for a Diverse Forest Ownership Structure in Projections of Forest Sustainability Indicators

Abstract: Abstract:In this study, we assessed the effect of a diverse ownership structure with different management strategies within and between owner categories in long-term projections of economic, ecological and social forest sustainability indicators, representing important ecosystem services, for two contrasting Swedish municipalities. This was done by comparing two scenarios: one where the diversity of management strategies was accounted for (Diverse) and one where it was not (Simple). The Diverse scenario result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Modern forestry was introduced relatively late, in 1958, when the first clear-cut was registered by the Swedish Forest Agency. Nowadays, commercial forestry is conducted on nearly 80% of the forest land [34]- [36]. Large parts of the Ångermanälven basin within the Vilhelmina municipality have been affected by timber rafting that, to some extent, continued until the 1980s.…”
Section: Methodsmentioning
confidence: 99%
“…Modern forestry was introduced relatively late, in 1958, when the first clear-cut was registered by the Swedish Forest Agency. Nowadays, commercial forestry is conducted on nearly 80% of the forest land [34]- [36]. Large parts of the Ångermanälven basin within the Vilhelmina municipality have been affected by timber rafting that, to some extent, continued until the 1980s.…”
Section: Methodsmentioning
confidence: 99%
“…Some scenario studies following the new trend have solely focused on including empirically grounded specifications reflecting current owner behavior without considering changes in external drivers (e.g., [14][15][16]). As a recent example, Eggers et al [16] accounted for the diversity of management strategies among owners when projecting the provisioning of ecosystem services in two Swedish municipalities. The results clearly showed that detailed differentiation of owners' management behavior makes a difference when projecting ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, land use and forests in Vilhelmina have been studied and described from various perspectives over the years cf. [25,66,67,[102][103][104][105][106][107][108][109][110][111]. This history gives a unique opportunity to combine and compare information from our study with other research to further analyze and learn about local forests from a municipal perspective.…”
Section: Data Overlay and Spatial Analysismentioning
confidence: 99%
“…Over 4000 km 2 are boreal forest land and of this area 3150 km 2 are classified as productive forests cf. [25]. Compilations and analyses for this study are made for the entire municipality as well as for our focus study area, which is in the eastern half of the municipality (4170 km 2 of which 2670 km 2 is forest land) (Figure 1).…”
Section: Case Study Areamentioning
confidence: 99%
See 1 more Smart Citation